The Effectiveness of PBL Assisted by EBM to Increase Students' Conceptual Understanding - Yustinus Maksimilianus Dhey Nesi; Endang Purwaningsih (Jurnal Pembelajaran Fisika, 2021)
Conceptual understanding involves students' abilities in the aspects of translation, interpretation, and extrapolation. A way to increase conceptual understanding is to use excel-based modeling (EBM). However, the use of excel-based modeling (EBM) has not been applied in physics learning at the junior high school level. This study aims to test the effectiveness of project-based learning assisted by excel-based modeling to increase students' conceptual understanding of wave material. The sample of this study were students of class VIII-1 junior high school who were selected using the purposive sampling technique. This study used a one-group pretest-posttest design. Research data determine the effectiveness of using excel-based modeling using a pretest and posttest in the form of 7 identical essay questions. The data obtained were analyzed using a paired-sample T-test. After the treatment, data on the increase in the value of each indicator of concept understanding were obtained, namely 91.18 (translation), 86.65 (interpretation), and 83.09 (extrapolation). In the end, excel-based modeling is quite effective in improving students' understanding of concepts.Keywords: Conceptual Understanding, Excel-based Modelling, Project-based Learning DOI: http://dx.doi.org/10.23960/jpf.v9.n1.202105